(untitled) - Tom Elliott (Cambridge, Massachusetts, 1996)
The book is divided into two main sections: organisms and infections; and covers all aspects of microbiology including bacteriology, virology, mycology and parasitology. It also contains zoonoses, the basics of antimicrobial chamotherapy, the fundametal of diagnostic laboratory methods
Keywords: communicable diseases - microbiology,medical microbiology - outlines, syllabi, etc,microbiology